(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Himalayas are one of the tallest mountains of the world. The length of its arc is measured to be nearly 2400 kilometers. The collision of two major tectonic plates was the root cause of the evolution of these mountains. Some of the known superlatives of the Himalayas are K2 and Nanga. The nature of the climate of India especially, North India is truly dependent on the Himalayas.The breadth of the mountains of the Himalayas is measured to be within a range of 240-330 kilometers. The range of the Himalayas covers the five major Asian counties. The overall area of the Himalayas is measured to be nearly 7,50,000 kilometers. The complex of the Himalayas includes the Hind Kush, Tien Shan, and the Pamirs etc. The current paper highlights the mountain units of the Himalaya.